Plasma of electric arc between electrodes from composite materials - Babich, I.L.; Boretskij, V.F.; Minakova, R.V.; Veklich, A.N. (Вопросы атомной науки и техники, 2008)
The investigations of the processes of the mass transfer in a discharge gap of electric arc and peculiarity of interactions of composite electrode surface with discharge plasma were carried out. The optical spectroscopy and metallographic techniques were used. The unique secondary structure of electrode surface was formed by plasma of an electric arc discharge in air at arc current under 100 A. Металографічними методами та методами оптичної спектроскопії досліджені процеси масопереносу у розрядному проміжку електричної дуги. Вивчена особливість взаємодії поверхні композиційних електродів з розрядною плазмою. Виявлена унікальна вторинна структура поверхні електродів під впливом дугового розряду в повітрі при силі струму до 100 А. Металлографическими методами и методами оптической спектроскопии исследованы процессы массопереноса в разрядном промежутке электрической дуги. Изучена особенность взаимодействия поверхности композиционных электродов с разрядной плазмой. Обнаружена уникальная вторичная структура поверхности электродов под влиянием дугового разряда в воздухе при силе тока до 100 А.